Underwater Versus Conventional Endoscopic Mucosal Resection for Colorectal Laterally Spreading Tumors: A Post Hoc Analysis of Efficacy - Quang Dinh Le; Nhan Quang Le; Duc Trong Quach (JGH Open, 2024)
ABSTRACT Background and Aims Underwater endoscopic mucosal resection (UEMR) has emerged as a promising alternative to conventional endoscopic mucosal resection (CEMR) for the treatment of colorectal laterally spreading tumors (LSTs). This study aimed to compare the efficacy and safety of UEMR and CEMR in managing LSTs measuring 10–30 mm. Methods A post hoc analysis was performed on 88 patients with 88 colorectal LSTs, who were randomly assigned to two treatment groups: 42 with CEMR and 46 with UEMR. The primary outcome was the rate of R0 resection, defined as the absence of neoplastic cells at the resection margin. The secondary outcomes included en bloc resection rates, procedure times, and postprocedural complications. The data were analyzed via chi‐square tests, t tests, and the Mann–Whitney U test where appropriate. Results No significant difference was found in the R0 resection rate between UEMR and CEMR. However, UEMR achieved a significantly higher en bloc resection rate, particularly for LSTs ranging from 20 to 30 mm (42.9% for CEMR vs. 100% for UEMR; p = 0.009). Additionally, UEMR resulted in a shorter median procedure time (85.0 s for UEMR vs. 207.5 s for CEMR; p < 0.001). There was no significant difference in bleeding complications or the number of clips used between the two groups. Conclusions Compared with CEMR, UEMR offers a higher en bloc resection rate and a shorter procedure time, particularly for larger lesions, without increasing the risk of complications. UEMR should be considered a preferred option for managing colorectal LSTs, especially those measuring 20–30 mm.